Role of W-site substitution on mechanical and electronic properties of cubic tungsten carbide. (8th January 2020) - Augustine, Anu Maria; Ravindran, P
Abstract: In order to understand the role of W-site substitution on properties of cubic tungsten carbide ( -WC), we have investigated the structural, mechanical, and electronic properties of WXC2 (X  =  Si, Sc, Ti, V, Cr, Ge, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Sn, Hf, Ta, Re, Os, Ir, Pt, Th, U) using first principles calculations based on density functional theory, within generalized gradient approximation. The structural optimization has carried out for all these compounds using force as well as stress minimization. The optimized structural parameters for experimentally known compounds are in good agreement with the available x-ray diffraction measurements and structural parameters for nineteen WXC2 compounds are newly predicted. The W-site substitution of the above-listed elements into -WC reduces the symmetry of the primitive lattice to tetragonal structure. The heat of formation ( ) and the mechanical stability studies are carried out to investigate the stability of these systems. The single-crystal elastic constants c ij, elastic moduli of the polycrystalline aggregates, anisotropy in elastic constants and related properties of the WXC2 materials have calculated and discussed in detail. The hardness of the above materials is predicted using two different criteria, based on the softest elastic mode as well as the Pugh's modulus ratio. There is a correlation in the hardness predicted from these two approaches except in the case of -WC. The chemical bonding interaction between the constituents is analysed using the density of states, crystal orbital Hamiltonian population, and charge density for selected systems. All these compounds are predicted to be metal and our calculations suggest that W-site substitutions do not improve the hardness of -WC. However, from the heat of formation studies, we have identified five new stable compounds such as CrWC2, NbWC2, ScWC2, YWC2, and UWC2 with reasonably good hardness and those need experimental verifications.